Identification and functional characterization of a β-glucosidase from Bacillus tequelensis BD69 expressed in bacterial and yeast heterologous systems - Raza, Ahmad; Pothula, Ratnasri; Abdelgaffar, Heba; Bashir, Saira; Jurat-Fuentes, Juan Luis (PeerJ, 2020)
Background The identification and characterization of novel β-glucosidase genes has attracted considerable attention because of their valuable use in a variety of industrial applications, ranging from biofuel production to improved digestibility of animal feed. We previously isolated a fiber-degrading strain of Bacillus tequelensis from buffalo dung samples, and the goal of the current work was to identify β-glucosidase genes in this strain. We describe the cloning and expression of a new β-glucosidase gene (Bteqβgluc) from Bacillus tequelensis strain BD69 in bacterial and yeast hosts. The recombinant Bteqβgluc were used to characterize specificity and activity parameters, and candidate active residues involved in hydrolysis of different substrates were identified through molecular docking. Methods The full length Bteqβgluc gene was cloned and expressed in Escherichia coli and Pichia pastoris cultures. Recombinant Bteqβgluc proteins were purified by immobilized metal affinity or anion exchange chromatography and used in β-glucosidase activity assays measuring hydrolysis of ρ-nitrophenyl-β-D-glucopyranoside (pNPG). Activity parameters were determined by testing relative β-glucosidase activity after incubation under different temperature and pH conditions. Candidate active residues in Bteqβgluc were identified using molecular operating environment (MOE) software. Results The cloned Bteqβgluc gene belongs to glycoside hydrolase (GH) family 4 and encoded a 54.35 kDa protein. Specific activity of the recombinant β-glucosidase was higher when expressed in P. pastoris (1,462.25 U/mg) than in E. coli (1,445.09 U/mg) hosts using same amount of enzyme. Optimum activity was detected at pH 5 and 50 °C. The activation energy (Ea) was 44.18 and 45.29 kJ/mol for Bteqβgluc produced by P. pastoris and E. coli, respectively. Results from other kinetic parameter determinations, including pKa for the ionizable groups in the active site, Gibbs free energy of activation (ΔG‡), entropy of activation (ΔS‡), Michaelis constant (Km) and maximum reaction velocity (Vmax) for pNPG hydrolysis support unique kinetics and functional characteristics that may be of interest for industrial applications. Molecular docking analysis identified Glu, Asn, Phe, Tyr, Thr and Gln residues as important in protein-ligand catalytic interactions.
Keywords: β-glucosidase; Bacillus tequelensis; Heterologous expression; Glucosidase kinetics; Thermodynamics